USING CHLORELLA PYRENOIDOSA FERTILIZER FOR CONTROLLING SOIL ACIDITY IN MELON CULTIVATION - MARGARETHA PRABA AULIA (CV KULTURA DIGITAL MEDIA, 2021)
Most of the agricultural lands in Indonesia are in the same condition, which is the decrease in soil fertility. Continuous supply of chemical fertilizers causes soil to become nutrient poor, microbial diversity poor, hardened, and not loose. Besides this soil damage is also characterized by acidic soil pH. Soil acidification can cause a decrease in crop yields. This study aims to determine the effect of Chlorella pyrenoidosa microalgae in recovery soil acidity and its effect on rice crop productivity. This research involved laboratory analysis and field analysis. Laboratory analysis was conducted by treating acidic soil using 3 types of treatment, namely treatment using lime, treatment using urea chemical fertilizer, and treatment using Chloten fertilizer (Chlorella pyrenoidosa). Based on the laboratory scale analysis conducted the best results in recovery soil acidity are Chloten fertilizer (Chlorella pyrenoidosa) because it improves soil pH from acid (4,5) to neutral pH (7) which is the optimal pH for soil.